CONTEXTUAL MEANING ON AVRIL LAVIGNE SELECTED SONGS - Hulu, Anna Maria (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2023)
This study aimed to find out the contextual meaning of expression on Avrillavigne selected songs. This research was designed by using descriptive qualitative method with descriptive approach to analyze the data that indicated to contextual meaning that found on AvrilLavigne selected songs. The source data of this research is song lyrics, which is the singer is AvrilLavigne, and researcher selected the songs of AvrilLavigne. The data was analyzed by using the technique of the data analysis: data condensation, data display, drawing and verifying conclusions. The data was collected by using documentation. The result of this study shows that contextual meaning of expressions were found on AvrilLavigne selected songs. It was found that there were 31 expressions that contain contextual meaning used in five song lyrics. Based on the finding, it is concluded that the contextual meaning and lexical meaning of expressions that contain contextual meaning on AvrilLavigne selected songs found is carried within words, phrase and sentences in five lyrics of AvrilLavigne selected songs. In conclusion in expressing her experience, a composer or songwriter manipulates words and or languages to create an appeal to the lyrics. Hopefully, through this study song loves, teachers, students, and all those people who like to listen songs to will be easy to understand the meaning and expressing of the song that contained in the songs they listen.